2000
DOI: 10.1074/jbc.m001859200
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Roles for Two Water Bridged Residues (Asp-98 and His-255) in the Active Site of Copper-containing Nitrite Reductase

Abstract: Two active site residues, Asp-98 and His-255, of copper-containing nitrite reductase (NIR) from Alcaligenes faecalis have been mutated to probe the catalytic mechanism. Three mutations at these two sites (D98N, H255D, and H255N) result in large reductions in activity relative to native NIR, suggesting that both residues are involved intimately in the reaction mechanism. Crystal structures of these mutants have been determined using data collected to better than 1.9-Å resolution. In the native structure, His-25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
154
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(163 citation statements)
references
References 35 publications
8
154
0
1
Order By: Relevance
“…Extensive spectroscopic and structural studies of CuNiRs (Strange et al, 1999;Boulanger et al, 2000;Boulanger & Murphy, 2001;Tocheva et al, 2004Tocheva et al, , 2007Antonyuk et al, 2005;Krzemiń ski et al, 2011;Wijma et al, 2006;Hough et al, 2008;Leferink et al, 2011Leferink et al, , 2012 have suggested a general catalytic mechanism in which bound water in the resting state is replaced by nitrite, and internal electron transfer occurs between the T1Cu and T2Cu sites. Two protons are required for the reaction, which are thought to be provided by Asp98 (Asp CAT ) and His255 (His CAT ) via a bridging water molecule, leading to cleavage of the bound NO 2 À to produce NO and H 2 O. Conformational rearrangements of Asp CAT have been proposed to be important in substrate guidance and proton transfer (Antonyuk et al, 2005), while His CAT may respond to the redox state.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive spectroscopic and structural studies of CuNiRs (Strange et al, 1999;Boulanger et al, 2000;Boulanger & Murphy, 2001;Tocheva et al, 2004Tocheva et al, , 2007Antonyuk et al, 2005;Krzemiń ski et al, 2011;Wijma et al, 2006;Hough et al, 2008;Leferink et al, 2011Leferink et al, , 2012 have suggested a general catalytic mechanism in which bound water in the resting state is replaced by nitrite, and internal electron transfer occurs between the T1Cu and T2Cu sites. Two protons are required for the reaction, which are thought to be provided by Asp98 (Asp CAT ) and His255 (His CAT ) via a bridging water molecule, leading to cleavage of the bound NO 2 À to produce NO and H 2 O. Conformational rearrangements of Asp CAT have been proposed to be important in substrate guidance and proton transfer (Antonyuk et al, 2005), while His CAT may respond to the redox state.…”
Section: Introductionmentioning
confidence: 99%
“…The normal catalytic product, NO, is thought to exit through these same channels. An isoleucine residue (Ile CAT ) that caps the active-site pocket has been proposed to provide steric constraints to ligand access and selectivity to ligand binding (Boulanger & Murphy, 2003;Tocheva et al, 2008), while critical aspartate (Asp CAT ) and histidine (His CAT ) residues are required for the correct ligand positioning, hydrogen bonding and proton delivery during catalysis (Antonyuk et al, 2005;Boulanger et al, 2000;Boulanger & Murphy, 2001). In Achromobacter cycloclastes nitrite reductase (AcNiR) these are the Ile257, Asp98 and His255 residues.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray crystal structures have been determined for the green NiRs from Achromobacter cycloclastes (AcNiR) (9,10) and Alcaligenes faecalis NiR (4,(11)(12)(13) and the blue Alcaligenes xylosoxidans (AxNiR) (14,15), for which an atomic resolution structure has been reported recently (5). For the green nitrite reductases, resolution of the structure has steadily improved with the highest resolution being 1.4 Å.…”
mentioning
confidence: 99%
“…The type 2 Cu ion (T2Cu) has (His) 3 -H 2 O (or OH Ϫ ) ligation with one of the His residues being provided by an adjacent monomer. Mutagenesis studies have shown that the active site pocket also has conserved aspartyl (Asp-98) and histidinyl (His-255) residues that are essential for enzymatic activity (4)(5)(6)(7) and an isoleucine (Ile-257) residue that is important for optimum positioning of nitrite before catalysis (8). The residues His-255 and Ile-257 are provided by the adjacent monomer.…”
mentioning
confidence: 99%